DAMPAK PROJECT-BASED LEARNING (PJBL) BERBASIS ETNO-STEM TERHADAP KETERAMPILAN BERPIKIR KREATIF MURID - Nanda Nur Kumairoh, Diah; Fauzi Hendratmoko, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low creative thinking skills of students in science learning encourages innovation in teaching. Learning with the Ethno-STEM based PjBL model has the potential to improve creative thinking skills through the application of Ethno-STEM based PjBL. This study used a one group pre-test post-test design, involving 32 eighth-grade students at SMP Sunan Giri Menganti. The research instrument was a pre-test post-test question sheet. The data were analyzed quantitatively using paired sample t-test, N-gain, and effect size to measure the improvement of creative thinking skills. The results of the study showed an increase in scores between the pre-test and post-test. With an average N-gain of 0.60, which falls into the moderate category, and an effect size of 3.76, indicating a large effect. The conclusion of this study is that the application of the Ethno-STEM based PjBL model is effective in improving students' creative thinking skills.